Analgesia and anesthesia in labor and delivery-II - Baheti, Dwarkadas (New Delhi : Jaypee Brothers Medical Publishers, 2014)
Anesthesiologists and anesthesia play a critical role in the modern labor and delivery unit. Cesarean deliveries require the participation of an anesthesia provider in the care of the parturient (and by extension, the fetus). In addition, the anesthesiologist plays a critical role in the care of many high-risk parturients. As part of the perinatal team.
Contents History of labor analgesia Minimum standards for providing anagelsia services Ultrasound filicitated neuraxial block in labor Initation of labor analgesia y otros
Incluye índice
Keywords: ANESTESIA